PENGARUH FREE CASH FLOW, KEPEMILIKAN INSTITUSIONAL, DAN UKURAN DEWAN TERHADAP MANAJEMEN LABA (Studi Kasus pada Perusahaan Sektor Keuangan yang terdaftar di Bursa Efek Indonesia Periode 2020-2024) - Cut Syahidathain Meutia Az Zahra; Wiwin Aminah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of free cash flow, institutional ownership, and board size on earnings management in financial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Earnings management is measured using the Modified Jones Model as a proxy for discretionary accruals. This research employs a quantitative method with purposive sampling and multiple linear regression analysis as the analytical tool. The results are expected to show that free cash flow, institutional ownership, and board size significantly affect earnings management both partially and simultaneously. These findings contribute to the academic literature and stakeholders in improving corporate governance quality in the financial sector.